DOES DIGITALIZATION AGGRANDIZE INCOME? THE INDONESIA FAMILY LIFE SURVEY FIFTH WAVE - Imam, Muhammad Kholisul; Januari, Anas Tania (Faculty of Business, Widya Mandala Surabaya Catholic University, Indonesia, 2021)
The COVID-19 pandemic has shaken Indonesia's macroeconomy. The economic growth experienced a contraction accompanied by an increase in poverty and unemployment. On the other hand, the COVID-19 pandemic also provides an opportunity for the growth of the digital economy. Digitalization that goes well will increase economic activity due to greater accessibility. However, there has been a decline in income during the pandemic. Therefore, this research aims to learn whether digitalization can improve income levels by understanding the impact of having a cell phone and accessing the internet for economic activities towards revenues. Here, the treatment effect is conducted to estimate the magnitude of that impact and identify the factors determining digitalization (have a cell phone and access the internet for economic activities). This research uses secondary data obtained from the Indonesia family life survey fifth wave. The result shows that the income of someone who can digitize is higher than that of non-digitalization participants, indicating the digitalization significantly contributes to increased revenues. Moreover, object perception for having a cell phone and accessing the internet for economic activities supports people's interest in digitalization mainly due to happiness, subjective well-being, and marital status.